ANALISIS HUBUNGAN PERSEPSI PENEGAK HUKUM (HAKIM) DENGAN PERSETUJUAN PENERAPAN RESTORATIVE JUSTICE DALAM PENYELESAIAN SENGKETA MEDIS - Tiffanny Pramita Apsari; Setyo Trisnadi (PT. Hasba Edukasi Mandiri, 2026)
Medical disputes are legal issues in the field of health that require fair and balanced resolution between medical personnel and patients. The Restorative Justice approach emerges as a non-litigation alternative that emphasizes restoring relationships and achieving peaceful agreements between the disputing parties. The success of this approach largely depends on the perception of law enforcers, particularly judges, who hold the authority in resolving such cases. This study analyzes the relationship between the perception of law enforcers (judges) and their approval of the application of Restorative Justice in resolving medical disputes at the North Jakarta District Court. The research employed an analytical observational method with a cross-sectional design involving 31 judges as respondents. The results showed that most judges had a good perception of Restorative Justice (87.1%) and the majority agreed with its implementation (83.9%). The Chi-Square test produced a p-value of 0.000, indicating a significant relationship between judges’ perception and their level of approval. These findings affirm that judges’ positive understanding of restorative justice principles plays a crucial role in promoting peaceful and humanistic settlement of medical disputes. However, practical implementation still faces challenges such as limited practical experience, lack of regulatory support, and public pressure. Therefore, it is necessary to enhance training and socialization for law enforcers so that the concept of Restorative Justice can be effectively and sustainably implemented.